2010
DOI: 10.1103/physrevlett.105.233904
|View full text |Cite
|
Sign up to set email alerts
|

Magnetized Spiral Chains of Plasmonic Ellipsoids for One-Way Optical Waveguides

Abstract: When a linear chain of plasmonic nano-particles is subject to longitudinal magnetic field, it exhibits optical Faraday rotation. If the magnetized nano-particles are plasmonic ellipsoids arranged as a spiral chain, the interplay between the Faraday rotation and the geometrical spiral rotation (structural chirality) can strongly enhance non-reciprocity. This interplay forms a waveguide that permits one way propagation only, within four disjoint frequency bands; two bands for each direction.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 14 publications
0
81
1
1
Order By: Relevance
“…Plasmonic microstructures possess the unique ability of confining light into deep-subwavelength scale and strong field reinforcement effect, which provides an excellent platform for the realization of nanoscale chipintegrated photonic devices [22]. Various schemes have been proposed to demonstrate chip-integrated all-optical diode in plasmonic microstructures, such as using graded plasmonic chains based on full retardation effect [23,24], magnetized spiral chains of plasmonic ellipsoids based on interplay between the Faraday rotation and the geometrical spiral rotation under excitation of a longitudinal magnetic field [25], one-way electromagnetic modes at the interface between two dissimilar plasmonic metals (or a dielectric photonic crystal and a plasmonic metal) under excitation of a static magnetic field [26,27], or nonlinear plasmonic crystals [28], In 2011, Fan et al reported an electromagnetic diode with a transmission contrast of 14.7 dB in a microwave transmission line consisting of three metallic ring resonators and a varactor [29]. In 2013, Sun et al achieved an electromagnetic diode with a transmission contrast of 17.36 dB in a microwave waveguide system with asymmetric absorption and a varactor as a nonlinear medium [16].…”
mentioning
confidence: 99%
“…Plasmonic microstructures possess the unique ability of confining light into deep-subwavelength scale and strong field reinforcement effect, which provides an excellent platform for the realization of nanoscale chipintegrated photonic devices [22]. Various schemes have been proposed to demonstrate chip-integrated all-optical diode in plasmonic microstructures, such as using graded plasmonic chains based on full retardation effect [23,24], magnetized spiral chains of plasmonic ellipsoids based on interplay between the Faraday rotation and the geometrical spiral rotation under excitation of a longitudinal magnetic field [25], one-way electromagnetic modes at the interface between two dissimilar plasmonic metals (or a dielectric photonic crystal and a plasmonic metal) under excitation of a static magnetic field [26,27], or nonlinear plasmonic crystals [28], In 2011, Fan et al reported an electromagnetic diode with a transmission contrast of 14.7 dB in a microwave transmission line consisting of three metallic ring resonators and a varactor [29]. In 2013, Sun et al achieved an electromagnetic diode with a transmission contrast of 17.36 dB in a microwave waveguide system with asymmetric absorption and a varactor as a nonlinear medium [16].…”
mentioning
confidence: 99%
“…Instead of solving det M k (ω) = 0 to obtain the dispersion relation [10,14,17], we may apply the eigen-response theory to evaluate the dispersion relation [15,18]. Similar to the eigen-response theory, we plot 1/ |λ| as a function of k and ω, where |λ| = |λ(k, ω)| is the smallest absolute value of the eigenvalue of the matrix M k (ω).…”
Section: Model and Methodsmentioning
confidence: 99%
“…It is easy to understand that T symmetry can be broken by external static magnetic field [5], while P symmetry can be broken by using asymmetric structures such as chiral structures [5,[10][11][12] or a symmetrical structure under external magnetic field of specific orientation [13]. However, spectral reciprocity can also be protected by a combination of symmetries such as spatial-temporal symmetries, which add more complexities in the design of non-reciprocal waveguides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This realization of one-way propagation is quite different from other proposals for onewave wave-guiding. [10][11][12][13][14] The remainder of this article is organized as follows: First, we use the formalism of Ref. 5 to determine the dispersion relations for the L and T waves in the presence of an anisotropic host and a static magnetic field.…”
Section: Introductionmentioning
confidence: 99%